A Network Analysis of the Relationships Between Behavioral Inhibition/Activation Systems and Problematic Mobile Phone Use - Gao, Lingfeng; Zhao, Wan; Chu, Xiaowei; Chen, Haide; Li, Weijian (Frontiers in Psychiatry, 2022)
Background It is of great concern to society that individuals can be vulnerable to problematic mobile phone use (PMPU). However, there are a few studies in the field evaluating associations between behavioral inhibition/activation systems (BIS/BAS) and PMPU, and the results have been inconsistent. This study aimed to explore the relationships between BIS/BAS and PMPU by network analysis. Methods A total of 891 young adults participated in the study. BIS/BAS and PMPU were assessed by using the behavioral inhibition and activation systems scale and smartphone application-based addiction scale, respectively. The structure of the BIS/BAS-PMPU network was characterized using “strength,” “closeness” and “betweenness” as centrality indices. Edge-weight accuracy and centrality stability were tested using a bootstrap procedure. Results The network analysis showed that “mood modification,” “tolerance” and “withdrawal symptoms” had high centrality. In addition, the positive connection between BIS and “mood modification” or “tolerance” and between BAS-fun seeking and “mood modification” or “conflict” were also shown in the BIS/BAS-PMPU network. Conclusion These findings shed light on the central and bridge components between the BIS/BAS and PMPU communities, providing new evidence relevant to potential mechanisms that account for how high-BIS or high-BAS individuals develop PMPU, and inspiring component-based PMPU prevention or interventions.